IDENTIFICATION OF CONCERNING BEHAVIORAL ASPECTS DECISIONS ON THE ACTUAL USE OF ELECTRONIC MONEY IN THE BABY BOOMER GENERATION - Panhar, Efram Syukurlowen; Ginting, Ginta; Andriyansah, Andriyansah (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
This research is a quantitative descriptive study which aims to identify behavioral aspects of the decision to use electronic money in the Baby Boomer generation. The research involved 100 people from the baby boomer generation and filled out a questionnaire using convenience sampling as a sampling technique. Hypothesis testing uses the SEM-PLS method. The research results show that perceived ease of use, perceived usefulness, and perceived risk partially have a significant effect on interest in use. The results of the indirect influence show that perceived ease of use, perceived usefulness, and perceived risk each have a significant effect on the actual use of the Gopay mobile application which is mediated by the usage interest variable. The managerial implications of the research show how to increase the actual use of the Gopay mobile application through perceived ease of use, perceived usefulness, perceived risk and interest in use. Therefore, it is necessary to improve the quality of service in the information system by tightening the user data privacy system, as well as adding features to attract user interest, namely GoPay balances become GoPay Savings by Jago in just two minutes and adding innovative features such as free transfers, transfer anywhere, pay digital service, and pay QRIS.